Hungarians in the Anglo-Boer War (Historia, 2021)
The Anglo-Boer War (1899–1902), also known as the South African War, had many Hungarian connections in the areas of economy, politics, and culture. Great Britain and the Boer Republics attempted to purchase agricultural products (especially horses and flour) in Hungary, to be used during the war. Hungarian journals and newspapers published a large number of articles and other features on the war, and outstanding Hungarian poets and novelists, as well as politicians and other public figures reflected on the conflict and expressed their pro-Boer, pro-British, or neutral opinions. Hungarians who served in the Boer commandos or who fought under the Union Jack in South Africa constitute the closest connection between the Carpathian Basin and the Anglo-Boer War. Seventeen Hungarians have been identified who took an active part in the war, the majority of them (twelve people), on the Boer side, while only five supported the British war effort. This article focuses on three of the Hungarian participants: Tibor Péchy, Albert Wass, and Albert Theophilus Duka. While Péchy and Wass were pro-Boer volunteers, Duka served in the British Army. After describing their South African activities, a comparison is made of the motivation for their participation in the Anglo-Boer War.  Die Anglo-Boereoorlog (1899–1902) het verskeie Hongaarse konneksies gehad op ekonomiese, politieke en kulturele gebied. Brittanje en die Boererepublieke het gepoog om landbouprodukte (veral perde en meel) in Hongarye, vir gebruik in die oorlog, aan te koop. Hongaarse joernale en koerante het ’n groot aantal artikels en rubrieke oor die oorlog gepubliseer, en vername Hongaarse digters en skrywers, sowel as politici en ander openbare figure, het oor die oorlog besin en hul pro-Boer, pro-Britse, of neutrale menings daaroor uitgedruk. Hongare wat in die Boerekommandos gedien het, óf diegene wat onder die Union Jack in Suid-Afrika geveg het, verteenwoordig die nouste band tussen die Karpatiese Kom en die Anglo-Boereoorlog. Sewentien Hongare wat aktief aan die oorlog deelgeneem het is geïdentifiseer; die meerderheid (twaalf) aan die Boere-kant, terwyl net vyf die Britse oorlogspoging gesteun het. Hierdie artikel fokus op drie van die Hongaarse deelnemers: Tibor Péchy, Albert Wass en Albert Theophilus Duka. Péchy en Wass was pro-Boer vrywilligers, met Duka wat in die Britse weermag gedien het. Hul Suid-Afrikaanse bedrywighede word beskryf, waarna ’n vergelyking getref word tussen die faktore wat hulle beweeg het om aan die Anglo-Boereoorlog deel te neem.
Keywords: Anglo-Boer/South African War; Count Albert Wass; Dr Albert Theophilus Duka; Félix Luzsénszky; Hungarians; Hungarian Revolution and War of Independence, 1848–1849; Lajos Kossuth; Tibor Péchy; President Paul Kruger; Anglo-Boereoorlog/Suid-Afrikaanse Oorlog; Graaf Albert Wass; Hongare; Hongaarse Revolusie en Vryheidsoorlog, 1848–1849